2008
DOI: 10.1371/journal.pmed.0050014
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Chlamydiaceae Species in Trachoma: Implications for Disease Pathogenesis and Control

Abstract: Background Chlamydia trachomatis is a unique obligate intracellular bacterium that remains the leading cause of sexually transmitted bacterial diseases and preventable blindness worldwide. Chronic ocular infections are referred to as trachoma, and predominate in developing countries. Since 2001, the World Health Organization has promoted control strategies including antibiotics, improved hygiene, and environmental measures with limited success. Consequently, a vaccine is urgently needed. Integral to vaccine de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 89 publications
2
63
1
Order By: Relevance
“…The evidence for DNA exchange inferred from comparative genomic studies correlates well with reports of mixed chlamydial infections. For instance, in addition to ocular strains found in patients with trachoma, urogenital strains have also been observed in single or mixed infections of the conjunctiva (129). Mixed infections are also prevalent in populations with a high propensity for acquiring STDs (108,111,(130)(131)(132)(133).…”
Section: Evidence Of Lgt Events Among Chlamydia Clinical Isolatesmentioning
confidence: 99%
“…The evidence for DNA exchange inferred from comparative genomic studies correlates well with reports of mixed chlamydial infections. For instance, in addition to ocular strains found in patients with trachoma, urogenital strains have also been observed in single or mixed infections of the conjunctiva (129). Mixed infections are also prevalent in populations with a high propensity for acquiring STDs (108,111,(130)(131)(132)(133).…”
Section: Evidence Of Lgt Events Among Chlamydia Clinical Isolatesmentioning
confidence: 99%
“…They are highly pathogenic and cause genital tract, ocular, and respiratory infections in humans (9,55). A key characteristic of Chlamydiae is their biphasic developmental cycle, in which the bacteria alternate between two morphologies: the elementary body and the reticulate body (1,31).…”
mentioning
confidence: 99%
“…It is possible that some of our patients who needed augmented treatments might be due to non-trachomatis Chlamydia infection, as non-trachomatis chlamydial conjunctivitis is thought more common than previously understood, and a longer course of antibiotic treatment than C. trachomatis infection was considered necessary to eradicate the organism. 25,26 In this study, we also observed that older patients had a tendency to require more augmented treatments, but the number of patients was too small to draw a definite conclusion. Further well-powered clinical studies with a larger number of participants are required to confirm this association.…”
Section: Resultsmentioning
confidence: 58%